2020
DOI: 10.1515/iss-2019-0016
|View full text |Cite
|
Sign up to set email alerts
|

Women in surgery: a web-based survey on career strategies and career satisfaction

Abstract: Women represent the majority of medical students in several countries. In any surgical specialty and above all in surgical leadership positions, women still remain disproportionally underrepresented. The objective of this study was to investigate female surgeons’ career advancement and satisfaction with training. A standardized questionnaire was devised and sent out via the web-based survey tool SurveyMonkey® to female surgeons in the German federal state of North Rhine-Westphalia. A total of 125 completed que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…A study by Seeman et al (2016) reports balancing surgical careers with family commitments is a major source of stress (Seeman et al , 2016). Likewise, among Austrian women in leadership positions, it has been shown that inadequate help with child care has been a barrier to career advancement (Radunz et al , 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A study by Seeman et al (2016) reports balancing surgical careers with family commitments is a major source of stress (Seeman et al , 2016). Likewise, among Austrian women in leadership positions, it has been shown that inadequate help with child care has been a barrier to career advancement (Radunz et al , 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Women make up more than half of medical doctors in several countries across the globe including the USA, the UK and Australia. Yet, despite gender equity in medical schools (Jena et al , 2015; Radunz et al , 2020; Sexton et al , 2012; Singh et al , 2020; Silver, 2018 and Silver et al , 2017; Temkin, 2020), there is a disparity in surgery and women remain disproportionally underrepresented in leadership positions in surgical specialties including professors, chairpersons or medical school deans (Battaglia et al , 2020; Burdine et al , 2019; Giuffrida et al , 2020; Keane et al , 2021; Olson, et al , 2021; Mueller, 2016; Sexton, 2012; Skinner et al , 2019; Yin et al , 2021). In the USA, studies have shown that 12% of Professors in academic surgery and 25% of surgical faculty are women (Battaglia et al , 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…There is no common understanding of the term "career strategy" in existing studies. The authors consider a career strategy (1) as a plan of human actions that facilitate career building (Lyusova, Seredintseva & Glukhova, 2019); (2) as a desired position, but without certain steps to achieve it (Radunz et al, 2020); (3) the values of a person, based on which he chooses that or another profession, for example, because of a high status in society instead of a high salary (Kalyanova, 2019). Such differences in the approaches to the study of career strategies allows to consider the problems of career building from many directions, and at the same time researcher's different understanding of the term "career strategy" complicates the systematizing of existing knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…The numbers and percentages of female medical students, physicians, surgical trainees, surgeons, and academics have been consistently increasing. 1 2 3 4 5 6 In Korea, women accounted for 38.7% of all graduates of the medical schools and the graduate schools of medicine in 2020, 7 and 22.8% of all physicians were female in 2018; however, only 8.9% of surgical physicians were women. 8 In the U.S., the Association of American Medical Colleges reported that 51% of all medical students in the U.S. were female in 2018, 9 and 35.2% of all active physicians were women in 2017, although they only accounted for 20.6% of surgeons.…”
Section: Introductionmentioning
confidence: 99%